Implications and emerging control strategies for ventilator-associated infections. Issue 3 (March 2015) - Loo, Ching-Yee; Lee, Wing-Hin; Young, Paul M; Cavaliere, Rosalia; Whitchurch, Cynthia B; Rohanizadeh, Ramin
<x xml:space="preserve">Abstract</x> Ventilator-associated pneumonia (VAP) remains a major burden to the healthcare system and intubated patients in intensive care units. In fact, VAP is responsible for at least 50% of prescribed antibiotics to patients who need mechanical ventilation. One of the factors contributing to VAP pathogenesis is believed to be rapid colonization of biofilm-forming pathogens such as Pseudomonas aeruginosa and Staphylococcus aureus on the surface of inserted endotracheal tubes. These biofilms serve as a protective environment for bacterial colonies and provide enhanced resistance towards many antibiotics. This review presents and discusses an overview of current strategies to inhibit the colonization and formation of biofilm on endotracheal tubes, including antibiotic treatment, surface modification and antimicrobial agent incorporation onto endotracheal tube materials.